2008
DOI: 10.1002/ajmg.a.32478
|View full text |Cite
|
Sign up to set email alerts
|

Extended follow‐up of the Finnish cartilage‐hair hypoplasia cohort confirms high incidence of non‐Hodgkin lymphoma and basal cell carcinoma

Abstract: Cartilage-hair hypoplasia (CHH) is an autosomal recessive chondrodysplasia with short stature, sparse hair and defective cell-mediated immunity. It is caused by mutations in the RMRP (ribonuclease mitochondrial RNA processing) gene, encoding the RNA component of the ribonuclease complex RNase MRP. The aim of this study was to further elucidate the risk and spectrum of cancer in CHH. A cohort of 123 Finnish patients with CHH (51 males) was followed for malignancy through the Finnish Cancer Registry. The number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 29 publications
2
59
0
2
Order By: Relevance
“…Despite including only 10 patients with AT, we observed a significantly increased relative risk of NHL, which is consistent with previous, good-quality evidence from larger AT cohorts. 10,13 Apart from cartilage hair hypoplasia, 12 the risk of cancer relative to the general population has not been previously quantified for the remaining PID classifications or PID entities. Although our findings support variation in NHL risk by the form of primary immunodeficiency, we had insufficient statistical power to reliably estimate NHL incidence for the rarer PID subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite including only 10 patients with AT, we observed a significantly increased relative risk of NHL, which is consistent with previous, good-quality evidence from larger AT cohorts. 10,13 Apart from cartilage hair hypoplasia, 12 the risk of cancer relative to the general population has not been previously quantified for the remaining PID classifications or PID entities. Although our findings support variation in NHL risk by the form of primary immunodeficiency, we had insufficient statistical power to reliably estimate NHL incidence for the rarer PID subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…7 PID has been associated with a markedly increased risk of cancer, in particular non-Hodgkin lymphoma (NHL). [8][9][10][11][12][13] However, the PID cancer risk profile is not well characterized because most previous studies have been nonpopulation-based, of small sample size, of limited follow-up, and without a matched comparison group. Other cancers that appear to be associated with specific forms of PID include stomach cancer with common variable immune deficiency (CVID), 8,11 leukemia with ataxia-telangiectasia (AT), 10,13 and nonmelanocytic skin cancer with cartilage-hair hypoplasia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 10 patients in the cohort developed basal cell carcinoma of the skin. 104 The authors concluded that there was a 7-fold increase overall cancer rate in patients with CHH compared with the normal population, with the risk of non-Hodgkin lymphoma and skin cancer being even higher. A predisposition for cancer has not been reported in TCS, which is not associated with hematologic manifestations.…”
Section: Ribosomal Dysfunction and Cancermentioning
confidence: 99%
“…Nevertheless, primary immune deficiency patients have been associated with a marked increased risk of cancer. Some types of cancers appear to be associated with specific forms of immunodeficiency including stomach cancer with common variable immune deficiency (CVID) (Kinlen et al, 1985;Mellemkjaer et al, 2002), leukemia with ataxiatelangiectasia (Morrell et al, 1986), and nonmelanocytic skin cancer with cartilage-hair hypoplasia (Taskinen et al, 2008). In a recent population-based study, the association of antibody deficiency with an increasing risk of leukemia, non-Hodgkin lymphoma and gastric cancer has been described (Vajdic et al, 2010).…”
Section: Immune Surveillance Of Chronic Lymphocytic Leukemiamentioning
confidence: 99%